BMP gradient along the intestinal villus axis controls zonated enterocyte and goblet cell states - Beumer, Joep; Puschhof, Jens; Yengej, Fjodor Yousef; Zhao, Lianzheng; Martinez-Silgado, Adriana; Blotenburg, Marloes; Begthel, Harry; Boot, Charelle; van Oudenaarden, Alexander; Chen, Ye-Guang; Clevers, Hans (Cell reports (Cambridge), 2022)
Intestinal epithelial cells derive from stem cells at the crypt base and travel along the crypt-villus axis to die at the villus tip. The two dominant villus epithelial cell types, absorptive enterocytes and mucous-secreting goblet cells, are mature when they exit crypts. Murine enterocytes switch functional cell states during migration along the villus. Here, we ask whether this zonation is driven by the bone morphogenetic protein (BMP) gradient, which increases toward the villus. Using human intestinal organoids, we show that BMP signaling controls the expression of zonated genes in enterocytes. We find that goblet cells display similar zonation involving antimicrobial genes. Using an inducible Bmpr1a knockout mouse model, we confirm that BMP controls these zonated genes in vivo. Our findings imply that local manipulation of BMP signal strength may be used to reset the enterocyte “rheostat” of carbohydrate versus lipid uptake and to control the antimicrobial response through goblet cells. [Display omitted] •Human intestinal lineages display divergent gene expression along the crypt-villus axis•Top villus cell functions are not accurately recapitulated in conventional organoids•BMP activation drives the expression of villus tip genes in human organoid cultures•Loss of Bmpr1a receptor in human organoids and mice reduces top villus gene expression Beumer et al. show that the bone morphogenetic protein (BMP) signaling pathway controls functional zonation of the major human intestinal epithelial lineages along the crypt-villus axis. A gene lipid uptake gene signature is enriched in the villus tip and could be therapeutically exploited with BMP inhibitors.